2000
DOI: 10.1007/s12043-000-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between deformation bleaching and mechanoluminescence in coloured alkali halide crystals

Abstract: The present paper reports the correlation between deformation bleaching of coloration and mechanoluminescence (ML) in coloured alkali halide crystals. When the -centre electrons captured by moving dislocations are picked up by holes, deep traps and other compatible traps, then deformation bleaching occurs. At the same time, radiative recombination of dislocation captured electrons with the holes gives rise to the mechanoluminescence. Expressions are derived for the strain dependence of the density of colour ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…So far as the deformation at constant strain rate is concerned, the results reported for the dependence of ML intensity on strain at different strain rates indicate the increase of ML intensity for a given time t with the strain rate [34]. The ML intensity in the plastic region has been found to increase linearly with the strain rate [34,[40][41][42][43]. These results are in accordance with Eq.…”
Section: Article In Presssupporting
confidence: 85%
See 2 more Smart Citations
“…So far as the deformation at constant strain rate is concerned, the results reported for the dependence of ML intensity on strain at different strain rates indicate the increase of ML intensity for a given time t with the strain rate [34]. The ML intensity in the plastic region has been found to increase linearly with the strain rate [34,[40][41][42][43]. These results are in accordance with Eq.…”
Section: Article In Presssupporting
confidence: 85%
“…Thus, U 0 =0.24 eV for KCl crystals. As the value of DU 0 is of the order of 0.10 eV for alkali halide crystals [26], (U 0 ÀDU 0 ) comes out to be of the order of 0.10 eV, which is comparable with the activation energy of the order of 0.10 obtained from the temperature dependence of ML of coloured alkali halide crystals, [25,[31][32][33][34]. As (U 0 ÀDU 0 ) is comparable to kT=0.026 eV at room temperature, it seems that the thermal activation energy will be sufficient to enable the interacting F-centre electrons to cross the potential barrier between the dislocation band and the interacting F-centre electrons lying in the expansion region of the edge of dislocations.…”
Section: Mechanism Of ML In Coloured Alkali Halide Crystalssupporting
confidence: 53%
See 1 more Smart Citation
“…Chandra et al [6] have studied the pressure and temperature dependence of the ML of g-irradiated alkali halide crystals. They have investigated the correlation between the deformation bleaching and ML [7] and the correlation between the acoustic emission and ML of the coloured alkali halide crystals [8]. Chandra et al [9][10][11] have shown that the mechanical interaction between the moving dislocations and F-centers is responsible for the ML of coloured alkali halide crystals.…”
Section: Introductionmentioning
confidence: 99%
“…These are corrected here.A corrected Figure 11 (page 889) is given below.References 13,14,16,18,19,20,21,22,24,25,26 The publisher apologizes for these errors. …”
mentioning
confidence: 99%